2015
DOI: 10.1002/pc.23834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasticizer on the electrical, thermal, and morphological properties of carbon black filled poly(propylene)

Abstract: Poly(propylene) (PP)/carbon black (CB) composites are melt-blended in a Brabender mixer with varying CB content. With the special-grade conductive CB, the surface resistivity of PP/CB composite was reduced by 13 orders of magnitudes by increasing the CB content from 0 to 15 wt%. The plasticizer poly(ethylene glycol) di-methyl ether (PEGDME) is used (0-5 wt%) to improve the dispersion of the CB in the polymer matrix and to reduce the surface resistivity of the composites. But the PEGDME plasticizer used here ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…It decreases the viscosity of the soft segment and results in a more uniform distribution of the carbon black particles due to the higher input of mixing energy. 39 According to the SEM micrographs of TPEE-mCB-EGMA containing CRFC (Figure 4(a) and 4(b)), with EGMA addition into TPEE-mCB containing binary system, delamination was observed between polymer and carbon fabrics due to reduction of wettability properties of neat TPEE. EGMA is an efficient reactive compatibilizer for PBT included polymer blends.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It decreases the viscosity of the soft segment and results in a more uniform distribution of the carbon black particles due to the higher input of mixing energy. 39 According to the SEM micrographs of TPEE-mCB-EGMA containing CRFC (Figure 4(a) and 4(b)), with EGMA addition into TPEE-mCB containing binary system, delamination was observed between polymer and carbon fabrics due to reduction of wettability properties of neat TPEE. EGMA is an efficient reactive compatibilizer for PBT included polymer blends.…”
Section: Resultsmentioning
confidence: 97%
“…It decreases the viscosity of the soft segment and results in a more uniform distribution of the carbon black particles due to the higher input of mixing energy. 39
Figure 3.SEM micrographs of the fracture surfaces of the multilayer CFRC with (a-b) Neat TPEE, (c-d) TPEE-mCB, (f-g) TPEE-mCB-Oil, (×5000 and ×10000 magnification, respectively) and polymer composite layer (e) TPEE-mCB, (h) TPEE-mCB-Oil, (×100000 and ×50000 magnification, respectively).
…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noted that the improvement to the electrical conductivity of PP with the addition of biochar is not to the level of other carbonaceous materials such as carbon black. 65 This could be due to the agglomeration of biochar or the presence of impurities and high ash content which could lead to the disruption of the conductive carbon network. 13 …”
Section: Effects Of Biochar Addition On the Characteristics Of Polyme...mentioning
confidence: 99%
“…However, it is noted that the improvement to the electrical conductivity of PP with the addition of biochar is not to the level of other carbonaceous materials such as carbon black. 65 This could be due to the agglomeration of biochar or the presence of impurities and high ash content which could lead to the disruption of the conductive carbon network. 13 Another study by Nan et al, (2015) 60 on the electrical conductivity of PVA/biochar composites revealed that PVA by itself has no electrical conductivity properties and the addition of small amounts of biochar to PVA (2% w/w) did little to improve the electrical conductivity of PVA.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…Some distinctive features of the fillers and matrix determine the end properties of the composites. For instance, filler dispersion and formation of a continuous conductive network with a threshold amount of the filler determine electrical conductivity of the final composites [14].…”
Section: Introductionmentioning
confidence: 99%